Heart rate does not accurately reflect power output during professional cycling competition - Palmer, G. S.; Martin, D. T.; McLean, B. D.; Bannan, S.; Lee, H.; Craig, N. P.; Hawley, J. A. (Medicine & Science in Sports & Exercise, 2000)
The relationship between heart rate and power output during a professional cycling road race was studied. Professional male cyclists (N = 5) rode two road race stages (RR1- 140 km and RR2 - 130 km) with power cranks attached to their cycles. The cranks stored heart rates and power for every second of the competition. The heart rate to power regression equation improved as longer periods of time were used. The prediction of power at high heart rates was poor. Mean heart rate might indicate whole body metabolic stress, but it does not accurately reflect power output in competitions. Implication. Heart rate does not reflect cycling power output.